Integrating Blended Learning and Peer Feedback in Teaching Writing Recount Text and Vocabulary - Nada Raudhotul Muthoharoh; Nurhaedah Gailea; Syafrizal Syafrizal (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
This research aims to investigate the integration of blended learning and peer feedback technique in teaching writing recount text and vocabulary mastery. The research applied quasi-experimental design. The population of this study was second grade of MTs Daarul Muqimien and 60 students as the samples. The data collection techniques used the test of writing skill and vocabulary mastery and the data of this research was analyze by using statistics Manova (Multivariate Analysis of Variants) with the helped of SPSS Statistics 22 Software. The result shows the significant value of students writing recount text by integrating blended learning and peer feedback technique is 0.000<0.05 F count 28.095, the significant value of students’ vocabulary mastery by integrating blended learning and peer feedback technique is 0.009<0.05 F count 7.203, and significant value of students writing recount text and vocabulary mastery by integrating blended learning and peer feedback technique is 0.000<0.05, F count 13.884. Based on the result, it concludes that there is a significant influence of students’ writing recount text and vocabulary mastery group through integrating blended learning and peer feedback technique.